Analysis of specificity of finished forms of antimicrobial preparations from Streptomyces albus - Тодосійчук, Тетяна Сергіївна; Покас, Олена Вікторівна (Eastern-European Journal of Enterprise Technologies, 2015)
The antimicrobial activity of the developed experimental forms of antiseptic preparations relatively common infectious agents was investigated. The complex action of the antiseptic solution from Streptomycesalbus UN 44, caused by the activity of bacteriolysins and antibiotic of the strain, defining a wide range of antimicrobial activity was shown. The maximum ability of such an antiseptic to destroy and inhibit the growth of microorganisms is determined in relation to the Gram-positive bacteria of the genera Corynebacterium, Bacillus, Streptococcus, Staphylococcus. The ability of the strain Streptomycesalbus UN 44 to accumulate an antibiotic in the cell and to secrete it exogenously was revealed. The leading fungistatic antibiotic activity in the finished forms of dry producer biomass and complex liquid antiseptic, the combination of substances with different mechanisms of antimicrobial action in the complex preparation were shown. Finished forms of antiseptic preparations (solution, extract, dry biomass) for use in veterinary, medicine, canning were proposed.